Yoga concept in Sri Guru Granth Sahib teachings: A conceptual frame development - Gurneet Kaur; Paran Gowda (Wolters Kluwer Medknow Publications, 2021)
Introduction: Sri Guru Granth Sahib (SGGS) or Adi Granth is the main Sikh scripture. The SGGS promote principles of liberty and impartiality to pursue the way to the Guru following the path of peace and prosperity. The Sikh code of conduct is known as Sikh Rehat Maryada. The code is an outline of the mandates of daily routine followed by every Sikh. It stipulates philosophy and mandates, according to the teachings of Sikhism's 10 gurus. The studies show the relationship between SGGS and Yoga. In SGGS the first phrase, the Mool mantra, starts with the idiom, Ek Onkar (AUM). The primary goal of SGGS is to achieve union with God by constantly remembering God's name. Practice is oriented around three "golden rules." Guru Nanak also hinted in his hymns about these chakras. Guru had talked about the Naval Lotus. In the heart (with the blooming of lotus), he has seen the Lord whose knowledge is spoken of as unfathomable. The way of the blooming of this lotus is described by Guru Nanak by saying that when with the help of "Guru-Sabad," the heart lotus blooms and fills with nectar which makes one contented. The need of the conceptual frame arises due to lack of scientific understanding of SGGS. Methodology: Scale development is a systematic process that is carried out at different stages of analysis. Following recommendations of DeVellis RF and Pasqual L scale development for the present study was accomplished in three stages namely item generation, theoretical analysis, and psychometric analysis the 30 items developed after content validity testing and cognitive interviews with select respondents. Results and Conclusion: Conceptual framework is developed through the Yogic teachings from SGGS versus Patanjali Yoga Sutra.